2014
DOI: 10.1016/j.rboe.2014.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Turco's injury: diagnosis and treatment

Abstract: The aim of this study was to alert doctors to the existence of Turco's injury and discus the existing treatments that have been described in the worldwide literature. A bibliographic survey of Lisfranc's injury and Turco's injury covering from 1985 to 2013 was conducted in the SciELO and PubMed databases. Among the 193 articles, those relating to bone-ligament injuries of the Lisfranc joint and high-energy trauma were excluded, as were the case reports. The patients selected were professional or amateur athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Lisfranc injuries are commonly misdiagnosed, resulting in inadequate treatment and debilitating degenerative arthritis [ 1 , 4 - 7 ]. In the present case study, a gravity stress lateral radiograph effectively identified an unstable Lisfranc injury that was obscured by weightbearing views.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lisfranc injuries are commonly misdiagnosed, resulting in inadequate treatment and debilitating degenerative arthritis [ 1 , 4 - 7 ]. In the present case study, a gravity stress lateral radiograph effectively identified an unstable Lisfranc injury that was obscured by weightbearing views.…”
Section: Discussionmentioning
confidence: 99%
“…The Lisfranc ligament which connects the medial cuneiform to the second metatarsal base is one of the major stabilizing structures of the tarsal-metatarsal joint. Injuries to the Lisfranc ligament are common in high energy motor vehicle accidents and in low energy sports injuries when the foot is twisted while bearing weight [ 1 , 7 ]. Despite this important role in stabilizing the foot and its transverse arch, injuries to the Lisfranc ligament are commonly misdiagnosed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations